2013
DOI: 10.1021/jm4008906
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Activity, Selectivity, and Liability Profiles in 5-Oxopyrrolopyridine DPP4 Inhibitors Leading to Clinical Candidate (Sa)-2-(3-(Aminomethyl)-4-(2,4-dichlorophenyl)-2-methyl-5-oxo-5H-pyrrolo[3,4-b]pyridin-6(7H)-yl)-N,N-dimethylacetamide (BMS-767778)

Abstract: Optimization of a 5-oxopyrrolopyridine series based upon structure-activity relationships (SARs) developed from our previous efforts on a number of related bicyclic series yielded compound 2s (BMS-767778) with an overall activity, selectivity, efficacy, PK, and developability profile suitable for progression into the clinic. SAR in the series and characterization of 2s are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…The synthesis and biological activities of the pyrrolo[3,4‐ b ]pyridines have been reported . Early, 4‐arylmethylene‐1‐substituted‐2,3‐dioxopyrrolidines were condensed with ethyl β‐aminocrotonate or 4‐aminopent‐3‐en‐2‐one to give adducts, which could be dehydrogenated to the corresponding pyrrolo[3,4‐ b ]pyridines .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and biological activities of the pyrrolo[3,4‐ b ]pyridines have been reported . Early, 4‐arylmethylene‐1‐substituted‐2,3‐dioxopyrrolidines were condensed with ethyl β‐aminocrotonate or 4‐aminopent‐3‐en‐2‐one to give adducts, which could be dehydrogenated to the corresponding pyrrolo[3,4‐ b ]pyridines .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the synthesis of molecules containing restricted and constrained PHPs via IMCR, followed by a domino process and subsequent CuAAC The pyrrolo [3,4-b]pyridin-5-one is an important fragment for building conformationally constrained peptidomimetics. Compounds incorporating this fused heterocycle exhibit a wide range of biological activities including anti-diabetic agents [16], anticancer, analgesic, and therapeutic agents for central nervous system-related diseases such as Alzheimer's, epilepsy, and schizophrenia [17][18][19][20]. Furthermore, Wager et al reported the synthesis of their analogs with brain-selective radioligand properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…The fused-type polyheterocyclic pyrrolo [3,4-b]pyridin-5-one system 1 is the structural core of various synthetic products showing interesting biological properties, such as the antiepileptic 2 [1] and the antihypoglycemic 3 [2] agents. Besides, the polyheterocyclic framework 1 is considered as a privileged aza analogue of the isoindolin-1-one system 4 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aim of this communication is to describe an efficient MW-assisted synthesis of eight new 6-nitrilmethyl-pyrrolo [3,4-b]pyridin-5-ones 8a-h via a domino process: aza Diels-Alder/Nacylation/aromatization (dehydration-decarboxylation) from their corresponding 2-aminonitrileoxazoles and maleic anhydride. Most of the reported methods to assemble pyrrolo [3,4-b]pyridin-5one based architectures involve multistep strategies as well as the use of harsh conditions-see for example the synthetic methodology reported by Devasthale et al [2]. However, various multicomponent reaction (MCR)-based synthetic strategies toward series of novel pyrrolo [3,4b]pyridin-5-one-containing polyheterocycles have been reported in the last decade by us [7][8][9][10][11][12][13][14] as an integral part of our ongoing research program.…”
Section: Introductionmentioning
confidence: 99%